(untitled) (Ustozlar uchun, 2026)
Article explores the phenomenon of semantic shifts and positional constraints within language, examining how meanings of words evolve over time and how their usage is influenced by their syntactic positions in sentences. Semantic shifts refer to the changes in meaning that words undergo, often due to cultural, social, or contextual factors. Positional constraints, on the other hand, pertain to the limitations imposed by a word’s syntactic role or placement within a sentence, which can affect its interpretation and the overall meaning conveyed.